2023
DOI: 10.1002/bse.3351
|View full text |Cite
|
Sign up to set email alerts
|

Employees' response to corporate greenwashing

Abstract: Research on corporate greenwashing has expanded rapidly in recent years. At the same time, emerging studies in related literatures have found that employees are seeking out firms that are social and environmental leaders, and employee activism within firms is growing. However, the effect of firms' exaggeration and misrepresentation of environmental claims, or greenwashing, on their own employees has been overlooked. Accordingly, we investigate greenwashing from an organizational psychology lens, exploring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Regarding CSR performance, few studies stressed that CSR decoupling increases firm's actual employee turnover (Scheidler et al, 2019), turnover intentions (Robertson, 2023)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding CSR performance, few studies stressed that CSR decoupling increases firm's actual employee turnover (Scheidler et al, 2019), turnover intentions (Robertson, 2023)…”
Section: Resultsmentioning
confidence: 99%
“…Regarding financial consequences, included studies recognized ROA as accounting‐based performance (Walker & Wan, 2012), interest rates and collateral loans (Cao et al, 2022), stock price crash risk (Liu et al, 2023), Tobin's Q (Chen & Dagestani, 2023;Hawn & Ioannou, 2016; Liu et al, 2023), cumulative abnormal returns (Du, 2015), economic performance score (Schons & Steinmeier, 2006), analyst forecast errors, cost of capital, and access to finance (Garcia‐Sanchez et al, 2021). Relying on CSR performance , CSR donations during the COVID‐19 crisis (Zhong et al, 2022), customer satisfaction (Ioannou et al, 2022), green trust (Chen & Chang, 2013) and firms' actual employee turnover and intentions (Robertson et al, 2023; Scheidler et al, 2019) were recognized. Moreover, as other firm variables, earnings management was included in one study (Garcia‐Sanchez et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The employee factor can also be dangerous for the company, as employees communicate their perceptions to the outside world and can be perceived as credible sources by other interest groups due to their direct connection to the company. It was also found that employees with a higher level of education in the area of the environment are more willing to leave the company in the event of greenwashing (Robertson et al, 2023).…”
Section: Impact Of Greenwashing On the Economymentioning
confidence: 99%
“…Additionally, there might be a positive moderating influence of green credit between ESG performance and CE. The phenomenon of "green washing" refers to companies exaggerating their ESG levels through various means to mislead investors and gain more profits 45 . This phenomenon is becoming increasingly prevalent in ESG reports and is a significant issue that cannot be ignored.…”
Section: The Role Of Green Creditmentioning
confidence: 99%